# Homework Help: Matrix/Error Proof?

1. Aug 29, 2010

### Gameowner

1. The problem statement, all variables and given/known data

Not too sure what this proof would be under, but am pretty sure it has to do with approximation errors, can anyone give me a hint as to how to even start this?

2. Relevant equations

3. The attempt at a solution

For the first one, my guess at the solution would be...

1)take the norm of both sides of x = Tx + b
2) then substitute in x^k = Tx^(k-1) + b into the x's
3)since x^k = Tx^(k-1) + b, we get norm( x^k = T(Tx^(k-1) + b) + b), which then we get infinite multiples of T. Hence T^k?

That's really wild guess at the solution, any help would be much appreciated

#### Attached Files:

• ###### q1.jpg
File size:
12.9 KB
Views:
95
2. Aug 29, 2010

### qbert

for the first part you might look at something like
|xk+1 - x| = |(Txk + b) - (Tx + b)| = |T(xk -x)|
and continue till k->0.

for the second, maybe try to establish something like
|xk - x| <= ||T|| |xk-1 - x| <= ||T|| ( |xk-1 - xk| + |xk - x|).

Then solve for |xk - x| in terms of |xk-1 - xk|.

And then try to figure out how to go from
|xk-1 - xk| to |x0 - x1|.

3. Sep 10, 2010

Dear qbert

For the 2nd part of the question. Are we meant to figure out how to go from |xk - xk-1| to |x1 - x0| rather than the given above |xk-1 - xk| to |x0 - x1|

my attempt at the question is as follows

||x(k) - x|| <= ||T|| ||x(k-1) - x(k)|| + ||T|| ||x(k) - x||

||x(k) - x|| - ||T|| ||x(k) - x|| <= ||T|| ||x(k-1) - x(k)||

||x(k) - x|| (1 - ||T||) <= ||T|| ||x(k-1) - x(k)||

solving for ||x(k) - x|| <= (||T||/(1 - ||T||)) ||x(k-1) - x(k)||

hence my query above.

Kind regards,
kcp

4. Sep 10, 2010

Dear qbert

For the 2nd part of the question. Are we meant to figure out how to go from |xk - xk-1| to |x1 - x0| rather than the given above |xk-1 - xk| to |x0 - x1|

my attempt at the question is as follows

||x(k) - x|| <= ||T|| ||x(k-1) - x(k)|| + ||T|| ||x(k) - x||

||x(k) - x|| - ||T|| ||x(k) - x|| <= ||T|| ||x(k-1) - x(k)||

||x(k) - x|| (1 - ||T||) <= ||T|| ||x(k-1) - x(k)||

solving for ||x(k) - x|| <= (||T||/(1 - ||T||)) ||x(k-1) - x(k)||

hence my query above.

Kind regards,
kcp